Dispersive liquid–liquid microextraction and diffuse reflectance-Fourier transform infrared spectroscopy for iodate determination in food grade salt and food samples. (30th January 2022) - Gupta, Manju; Jain, Archana; Verma, Krishna K.
Graphical abstract: Highlights: FT-IR enabled integrating unperturbed band inazo dye. Solvent polarity and pH of final solution do not interfere. Response surface methodology employed for optimization of reactions used. Method applied to real samples of food grade salt, health supplements, and vegetables. Sensitivity of FT-IR method found comparable or better than spectrophotometry. Abstract: A novel method based on diffused reflectance Fourier-transform infrared spectroscopy (DRS-FTIR) was employed for iodate determination in food grade salt and food products. The method attained sensitivity that was comparable to or better than that in most of the contemporary spectrophotometric methods. This was realized through a combination of azo dye formation and dispersive liquid–liquid microextraction of dye when a 37-fold enrichment was obtained. FT-IR enabled integrating alternative target peak, and freedom in sample solvent composition relative to UV–visible spectrophotometry where the solvent polarity, pH, and presence of ions may affect the spectral properties of the measurable coloured species. Food samples containing iodide or covalently bonded iodine were oxidized with alkaline permanganate for mineralization and iodate formation. Optimization of both reaction conditions was carried out by means of response surface methodology. The method had a linear range 0.04–10 mg kg −1 iodate and limit of detection of 4.4 µg kg −1 .